2010
DOI: 10.1186/1741-7015-8-32
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and depressive symptoms in adolescents: a prospective study

Abstract: BackgroundThe frequency of mental illness amongst adolescents and its potential long-term consequences make it an important topic to research in relation to risk and protective factors. Research on the relationship between physical activity and depressive symptoms in adolescents is limited. There is a particular lack of evidence from longitudinal studies. This study examines the relationship between depression and physical activity using the Research with East London Adolescents: Community Health Survey (RELAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
166
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(186 citation statements)
references
References 25 publications
15
166
1
4
Order By: Relevance
“…Previous findings have shown that physical activity is related to a variety of emotional problems, including depression [9,16,18]. However, a three-year follow-up study of Sagatun et al found that physical activity was weakly associated with mental health in adolescents [14].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Previous findings have shown that physical activity is related to a variety of emotional problems, including depression [9,16,18]. However, a three-year follow-up study of Sagatun et al found that physical activity was weakly associated with mental health in adolescents [14].…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have shown that physical activity has a range of positive psychological and physiological health benefits for adolescents and is an important component of a healthy lifestyle [9][10][11][12][13].However,the frequency of physical activity and exercise seem to decrease from childhood to adolescence, especially in girls [14,15]. Cross-sectional and longitudinal studies have stated that physical activity is beneficial in relation to depression in adolescents [9,[16][17][18]. Beneficial mechanisms explained by biological factors suggest that the relationship between physical activity and depression is mediated by acute physiological responses including an increase in endorphin production, monoamine circulation, or lower responses from stress [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in addition to the fact that only activities outside school hours were measured. Even though less variation in intensity and duration of physical activity occurs among adolescents during physical education classes, some students may be more active than others during free times at school (27). Objective measures that monitor energy expenditure can provide more comprehensive, quantitative assessments of physical activity.…”
Section: Discussionmentioning
confidence: 99%